G510(P) The changing indications for nighttime respiratory support in children with duchenne muscular dystrophy. (May 2019) - Speyer, F; Krygier, S; Lowe, P; Walker, A; Evans, H
Abstract : Background: Children with Duchenne Muscular Dystrophy (DMD) are predisposed to sleep disordered breathing (SDB), traditionally described as predominantly being hypoventilation secondary to muscle weakness. The British Thoracic Society (BTS) guidelines 2012 provide recommendations for the respiratory management of children with neuromuscular disease. Indications for overnight sleep monitoring include children with Forced Vital Capacity (FVC) <60% predicted, loss of ambulation because of progressive muscle weakness, symptoms of obstructive sleep apnoea (OSA) or hypoventilation, diaphragmatic weakness, or rigid spine syndrome. Our clinical practice is to screen proactively all boys with DMD for SDB who meet the above criteria. Those with SDB should be offered non invasive ventilation (NIV). Method: Retrospective case note review evaluating our current cohort of children with DMD receiving nighttime NIV and the indications for this. Results: Seven of 145 children currently receiving NIV have DMD, median age 15 years (range 11–18 years). All boys had undergone cardiorespiratory sleep studies because of clinical concerns about SDB. Median apnoea hypopnea index (AHI) prior to starting NIV was 11.6 (range 3.3–29.6). This predominantly consisted of obstructive events with a median obstructive AHI of 11.3 (range 3.3–27.6). 4% oxygen desaturation indices were elevated in 5 boys median 4.7 (range 2.4–10.7). Median transcutaneous carbon dioxide levels were 5.5 (range 4.9–6.9). Median FVC was relatively well preserved: median 1.38 l (range 1.13–2.87 l). Median Body Mass Index at the time of sleep study was ≥91 st centile in all 7 boys, and ≥97 th centile in 5 boys. 4 boys were receiving steroids for their neuromuscular disease at the time of starting NIV. 5 boys started on CPAP in view of preserved lung function and 2 on BIPAP. 2 have since developed hypoventilation and switching to BIPAP has been recommended. Conclusions: Whilst the BTS guidelines suggest progressive muscle weakness leads to respiratory failure and diurnal hypoventilation, our cohort suggests that OSA is the main indication for starting NIV; possibly secondary to steroids (use to treat DMD) and immobility. This service evaluation suggests our screening focus should be towards early detection of OSA, possibly best evaluated using multi-channel cardiorespiratory studies. Further prospective studies examining the relationship between steroid use and development of OSA should be considered.